2009
DOI: 10.2478/s11696-009-0032-8
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid profile of Trichosanthes kirilowii Maxim. seed oil

Abstract: Fatty acid profile data for refined cold-pressed Trichosanthes kirilowii Maxim. seed oil, in comparison to other commercially available oils — olive, rapeseed and camellia, are presented. Trichosanthes kirilowii Maxim. seed oil has high oleic and linoleic acid content and high polyunsaturated acid content. Squalene elutes as a distinct peak in the GC chromatograph. For a positive identification, MS detection was used. In the samples analyzed, squalene occurred in the range of 57.4–68.2 mg g−1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 42 publications
1
5
7
Order By: Relevance
“…The n-6/n-3 PUFA ratio has been recommended to be below 4 in human diets. In this study, the n-6/n-3 ratio was 1.01(Changxing), 1.00 (Quzhou), 0.92 (Yuexi), 0.87 (Dongzhi), respectively, which is inconsistent with the results of Wang et al [1] who reported a ratio of more than 4. The content of SFA was 5.02-6.70% of the total fatty acids, and significantly lower than the 12.1% reported by Wang et al [1].…”
Section: Fatty Acid Composition Of T Kirilowii Seed Oilcontrasting
confidence: 99%
See 4 more Smart Citations
“…The n-6/n-3 PUFA ratio has been recommended to be below 4 in human diets. In this study, the n-6/n-3 ratio was 1.01(Changxing), 1.00 (Quzhou), 0.92 (Yuexi), 0.87 (Dongzhi), respectively, which is inconsistent with the results of Wang et al [1] who reported a ratio of more than 4. The content of SFA was 5.02-6.70% of the total fatty acids, and significantly lower than the 12.1% reported by Wang et al [1].…”
Section: Fatty Acid Composition Of T Kirilowii Seed Oilcontrasting
confidence: 99%
“…The LA content in the present study was significantly lower than that determined by Wang et al [1] who found LA at 49.32% of the total seed oil. Oil from Quzhou seeds had the highest LA content (38.66%), while Changxing seeds had the lowest (33.09%).…”
Section: Fatty Acid Composition Of T Kirilowii Seed Oilcontrasting
confidence: 94%
See 3 more Smart Citations